1986
DOI: 10.1111/j.1399-6576.1986.tb02404.x
|View full text |Cite
|
Sign up to set email alerts
|

Clonidine and the sympatico‐adrenal response to coronary artery by‐pass surgery

Abstract: Clonidine was administered intravenously in an attempt to limit sympatico-adrenal activity and thereby reduce the incidence of arterial hypertension associated with coronary artery by-pass graft surgery (CABG). Forty patients scheduled for CABG were assigned to two groups. Twenty patients received clonidine 4 micrograms kg-1 before surgery, 2 micrograms kg-1 after cardiopulmonary by-pass and 1 microgram kg-1 when the skin was sutured. The other 20 patients served as controls. All patients were anesthetized wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
17
2
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(23 citation statements)
references
References 34 publications
3
17
2
1
Order By: Relevance
“…It is therefore conceivable that because dexmedetomidine attenuates stress-induced increases in circulating norepinephrine, it may maintain renal blood flow and glomerular filtration. Indeed, it is well established that the administration of a-2 adrenergic agonists can inhibit the surgical stress response [15][16][17] and thereby protect the kidney against the detrimental effects of adrenergic-mediated vasoconstriction [18]. There also may be direct vascular effects in the kidney.…”
Section: Discussionmentioning
confidence: 98%
“…It is therefore conceivable that because dexmedetomidine attenuates stress-induced increases in circulating norepinephrine, it may maintain renal blood flow and glomerular filtration. Indeed, it is well established that the administration of a-2 adrenergic agonists can inhibit the surgical stress response [15][16][17] and thereby protect the kidney against the detrimental effects of adrenergic-mediated vasoconstriction [18]. There also may be direct vascular effects in the kidney.…”
Section: Discussionmentioning
confidence: 98%
“…It is conceivable that dexmedetomidine attenuates surgical stress-induced increases in circulating epinephrine and norepinephrine and maintain renal blood flow and glomerular filtration. Therefore, it can protect the kidney against the adrenergic-mediated vasoconstriction by activation of α-2c receptors in the wall of vascular smooth muscle [8,30,31]. Dexmedetomidine can also exert direct vascular effects in the kidneys by decreasing the sympathetically mediated presynaptic release of norepinephrine in the kidneys, which could promote renal arterial vasodilatation [32].…”
Section: Discussionmentioning
confidence: 99%
“…However, it was previously reported that dexmedetomidine decreases the sympathetically mediated presynaptic release of norepinephrine in the kidney, attenuates stress-induced increases in circulating norepinephrine, and may maintain renal blood flow and glomerular filtration. [26] Indeed, it is well established that the administration of α 2 -adrenergic agonists can inhibit the surgical stress response [27][28][29] and thereby protect the kidney against the detrimental effects of adrenergicmediated vasoconstriction. [30] Dexmedetomidine could promote renal arterial vasodilatation as well.…”
Section: Discussionmentioning
confidence: 99%